2000
DOI: 10.7863/jum.2000.19.11.727
|View full text |Cite
|
Sign up to set email alerts
|

Common bile duct measurements in an elderly population.

Abstract: valuation of the CBD has been performed routinely with ultrasonography for at least 20 years. Within this time period numerous articles have been published describing the changes in caliber of the CBD related to various factors, including hepatobiliary disease, cholelithiasis, 1-3 patient's age, 4-6 and associated renal disease 7 or liver transplantation. 8 Extrinsic factors, such as time of day, 9 respiration, 10 or patient positioning during the examination, 11 also have been shown to affect the caliber of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 16 publications
3
56
1
6
Order By: Relevance
“…La disponibilidad de exámenes diagnós-ticos que permitan una adecuada evaluación y medición del CBC y la correlación con los parámetros de normalidad permite distinguir la presencia de colestasis secundaria a obstrucción frente a la colestasis no obstructiva (1, 3), aunque existe una plétora de literatura publicada en relación con el tamaño normal del CBC, con gran heterogeneidad en cuanto al diseño, la técnica de medición (dentro de los cuales los más utilizados actualmente incluyen: la ecografía transabdominal [ (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), los cuales han permitido fijar el límite superior normal, convencionalmente en 6 mm, aunque es algo arbitrario y dependiente de diferentes factores (edad, antecedentes quirúrgicos, técnica de medición, sexo, peso, realización de la medida posprandial, consumo de medicamentos, entre otros) (17)(18)(19).…”
Section: Introductionunclassified
“…La disponibilidad de exámenes diagnós-ticos que permitan una adecuada evaluación y medición del CBC y la correlación con los parámetros de normalidad permite distinguir la presencia de colestasis secundaria a obstrucción frente a la colestasis no obstructiva (1, 3), aunque existe una plétora de literatura publicada en relación con el tamaño normal del CBC, con gran heterogeneidad en cuanto al diseño, la técnica de medición (dentro de los cuales los más utilizados actualmente incluyen: la ecografía transabdominal [ (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), los cuales han permitido fijar el límite superior normal, convencionalmente en 6 mm, aunque es algo arbitrario y dependiente de diferentes factores (edad, antecedentes quirúrgicos, técnica de medición, sexo, peso, realización de la medida posprandial, consumo de medicamentos, entre otros) (17)(18)(19).…”
Section: Introductionunclassified
“…Finally, magnification and duct distension by contrast, used in ERCP and transhepatic cholangiography, may overestimate duct size [8] . Several studies in the last 20 years reported an increase in the CBD diameter in older patients, even if with consistent variability [6,7,9,10,12] . Based on autoptic observations, some authors identified loss of elastic fibers and proximal compensatory dilatation due to distal sclerosis as potential causes of the phenomenon [13] .…”
Section: Causes Of Biliary Dilatationmentioning
confidence: 99%
“…A variety of factors can influence bile duct size, prominently imag ing modality, age [7][8][9][10] and prior cholecystectomy. In transabdominal ultrasound (TUS), distal CBD may be difficult to visualize because of bowel gas, thus resulting in underestimation of duct size compared to other imaging techniques as computed tomography (CT), magnetic resonance cholangiopancreatography (MRCP), endoscopic retrograde cholangiopancreatography (ERCP) or percutaneous transhepatic cholangiography (PTC) [11] .…”
Section: Causes Of Biliary Dilatationmentioning
confidence: 99%
“…Perret 5 evaluated CBD in subjects aged 60-96 years and found significant increase with age. Kaim 6 reported CBD size from 2.1-9.5 mm in subjects of 45-75 years.…”
Section: Dicussionmentioning
confidence: 99%
“…Other sonographic studies established 4mm as normal mean CBD diameter at age of 40 years, 5mm at 50 years and 8mm at 80 years. [3][4][5][6] In 2003 Bachar 7 published that the width of CBD ranged from 1-8.6 and it dilated 0.04 mm/year. Horrow and associates 8 observed no increase in CBD with age.…”
Section: Introductionmentioning
confidence: 99%